A Grammar of Kuuk Thaayorre - Gaby, Alice R. (Mouton Grammar Library [MGL], 2017)
This grammar offers a comprehensive description of Kuuk Thaayorre, a Paman language spoken on the west coast of Cape York Peninsula, Australia. The Paman languages of Cape York have long been recognized for their exhibition of considerable phonological, semantic and morphosyntactic change (e.g. Hale 1964, Dixon 1980). Yet there has until now been no published full reference grammar of a language from this area (some excellent dictionaries, theses and sketch grammars notwithstanding, e.g. Hall 1972, Alpher 1973, 1991, Crowley 1983, Kilham et al. 1986, Sutton 1995, Smith & Johnson 2000). On the basis of elicited data, narrative and semi-spontaneous conversation recorded between 2002 and 2008, as well as archival materials, this grammar details the phonetics and phonology, morphosyntax, lexical and constructional semantics and pragmatics of one of the few indigenous Australian languages still used as a primary means of communication. Kuuk Thaayorre possesses features of typological interest at each of these levels